2017
DOI: 10.1097/mph.0000000000000761
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior Rating Inventory of Executive Function (BRIEF) to Identify Pediatric Acute Lymphoblastic Leukemia (ALL) Survivors At Risk for Neurocognitive Impairment

Abstract: Neurocognitive problems, including executive dysfunction, are potential late effects of pediatric acute lymphoblastic leukemia (ALL) treatment. Surveillance for neurocognitive impairment in a timely and efficient manner is imperative to ongoing clinical care. We sought to determine if the Behavior Rating Inventory of Executive Function (BRIEF) Parent Form identified leukemia survivors with cognitive impairment. In this 28-site cross-sectional study, parents of 256 children, a mean of 8.9 ± 2.2 years after trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
(39 reference statements)
2
8
0
Order By: Relevance
“…Graef et al (27) also found that childhood cancer survivors have more anxiety, depression, and antisocial behaviors. Warris et al (28), Viola et al (29), and Plas et al (30) also showed more behavioral and emotional problems in children with AML after the treatment, which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Graef et al (27) also found that childhood cancer survivors have more anxiety, depression, and antisocial behaviors. Warris et al (28), Viola et al (29), and Plas et al (30) also showed more behavioral and emotional problems in children with AML after the treatment, which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with two other studies that have investigated the use of parent-report measures as surveillance tools for identification of pediatric leukemia and brain tumor survivors with neurocognitive or learning problems [11, 12]. As in the current study, these measures had good specificity but were not sensitive enough to identify survivors with negative outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…[11] Similarly, in another study parent-completed BRIEF questionnaires demonstrated good specificity, but results were not sensitive enough to identify those leukemia survivors demonstrating real-life difficulties in the form of receiving special education services or problems with attention. [12]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring batteries that are sensitive and time efficient will be necessary to follow these patients. Other studies have examined the utility of neurocognitive monitoring or screening batteries in long-term survivors of leukemia (Boulet-Craig et al, 2018;Viola et al, 2017) or various pediatric cancers (Balsamo et al, 2019;Bull et al, 2015;Krull et al, 2008), and batteries that are sensitive to impairments starting early in treatment and continuing into survivorship are an area of active research (Sands et al, 2017). Results from the current study and previous research suggest that performance measures and parent/ teacher ratings of attention, executive functioning, and learning are important to include in a battery.…”
Section: Discussionmentioning
confidence: 75%